The Relationship Between Anxiety and Work Motivation for Nurses During the COVID-19 Pandemic at Lumajang Islamic Hospital - Muhammad Dafid Alfarizy; Suhari; Widya Addiarto (KHD Production, 2023)
The Covid-19 pandemic in Wuhan has had an impact on the whole world, the incidence of Covid-19 is increasing and increasing the atmosphere of anxiety, and uncertainty, especially for health workers. This study is an analytical descriptive, while the research design is cross-sectional, the data is taken by distributing questionnaires in the form of symptom questions and positive questions, distributed to nurses at the Lumajang Islamic Hospital which will be held from 3 to 6 September 2021 a population of 78 nurses, sample 35 respondents were studied and taken by purposive sampling. Data collection includes coding, editing, and tabulating, then the data is analyzed manually and computer with Spearman rank. COVID-19 cases at the Lumajang Islamic Hospital in 2021 3 nurses who were positive for COVID-19. Of the 35 respondents studied, most (82.9%) were women, while the education level was mostly (65.7%) with Diploma 3 education, most of them (54.3%) > 5 years, the average type of room (34.3%) was in COVID-19 Isolation. and non-Covid-19 Analysis of research results using Spearman rank obtained p 0.05, namely p = 0.045 with r-0.341 which means there is a relationship between anxiety and nurses' work motivation. It is hoped that the Lumajang Islamic Hospital will provide career paths and reward/future guarantees for health workers.